Prediction of body temperature using infrared thermometer in an alpaca herd (Arequipa, Peru) - Eduardo V., Gabriela (2021)
The infrared body temperature of 50 alpacas was evaluated in a herd of 155 male Huacaya alpacas at the Alpaca Development Center (CEDAT - Toccra) in Arequipa, Peru. An infrared thermometer was used on the nostrils, inner ear zone, middle ear zone and abdomen and a rectal thermometer to measure body temperature. Besides, ambient temperature was also recorded. The best predictive model of body temperature in alpacas was sought to be determined by regression analysis. The predictive models showed that the temperature variables of the inner ear zone and environmental temperature give a better prediction of body temperature in alpacas. It is concluded that it is possible to predict body temperature using infrared thermography.